UJI EFEK EKSTRAK ETANOL 70% DAUN BAWANG KUCAI (Allium tuberosum Rottl. ex Spreng) TERHADAP PENURUNAN LOW – DENSITY LIPOPROTEIN (LDL) SERUM TIKUS PUTIH JANTAN (Rattus norvegicus) GALUR WISTAR - ., Igri Septian Risky (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background : Garlic chives (Allium tuberosum Rottl ex Spreng) containorganosulphur and secondary metabolite that have an inhibitory effect onHMG-CoA reductase and serum Low-Density Lipoprotein lowering property.Objective: To investigate the effect of Garlic chives extract on serum LDLand to determine the effective dose to lower serum LDL in comparison withpravastatin Method: This research was an in vivo experimental study.Twenty five wistar rats were randomized into 5 groups, positive control group(pravastatin), negative control group (CMC 1%), dose I (0,0218 g/200gBW),dose II (0,04365 g/200gBW), Dose III (0,0873 g/200gBW). All rats were givenhigh cholesterol diet for 14 days to induce higher LDL level. The data wasanalyzed with One-way anova and LSD post hoc test. Result : Statisticalanalysis showed significant difference between average LDL level fromcontrol groups (negative and positive) and dose I, Dose II, and Dose IIIGroups (p<0,05) at day-42. The effective dose was 0,0218 g/200gBW.Conclusion: Ethanol 70% extract of garlic chives has serum low-densitylipoprotein lowering effect in rats and dose of 0,0218 g/200gBW showedequal effectivity with pravastatin Key Words: Allium tuberosum Rotll ex Spreng, Eth anol 70% extract of garlic chives,high cholesterol diet, Low-Density Lipoprotein (LDL) level lowering effect 1) Medical School, Faculty of Medicine, Tanjungpura UniversityPontianak, West Kalimantan 2) Pharmacy School, Faculty Of medicine, Tanjungpura UniversityPontianak, West Kalimantan 3) Departement of Medical Physiology, Medical School, Faculty ofMedicine, Tanjungpura University Pontianak, West Kalimantan